2021
DOI: 10.3390/en14061649
|View full text |Cite
|
Sign up to set email alerts
|

Suggesting a Stochastic Fractal Search Paradigm in Combination with Artificial Neural Network for Early Prediction of Cooling Load in Residential Buildings

Abstract: Early prediction of thermal loads plays an essential role in analyzing energy-efficient buildings’ energy performance. On the other hand, stochastic algorithms have recently shown high proficiency in dealing with this issue. These are the reasons that this study is dedicated to evaluating an innovative hybrid method for predicting the cooling load (CL) in buildings with residential usage. The proposed model is a combination of artificial neural networks and stochastic fractal search (SFS–ANNs). Two benchmark a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 147 publications
0
10
0
Order By: Relevance
“…Results indicate that the Gaussian process is a valid approach for the prediction of building heating and cooling demand. The performance of artificial neural networks for HL and CL prediction was enhanced by (Moayedi et al, 2021) using genetic algorithms and imperialist competition algorithms. Results indicated that the optimization approach significantly improved the performance of the model, with the imperialist competition algorithms showing better results than GA in this case.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results indicate that the Gaussian process is a valid approach for the prediction of building heating and cooling demand. The performance of artificial neural networks for HL and CL prediction was enhanced by (Moayedi et al, 2021) using genetic algorithms and imperialist competition algorithms. Results indicated that the optimization approach significantly improved the performance of the model, with the imperialist competition algorithms showing better results than GA in this case.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Air quality data (CO, SO 2 , O 3 , NO 2 and PM 2.5 ) of Taiwan Environmental Protection Administration analysed and concluded that the proposed multi-step fuzzy time series (MSFT) technique showed better results compared with seven predicting methods. In terms of effectiveness for a predictive approach, based on the fuzzy concept with Fractals techniques outperformed in contrast of classic fuzzy time series, linear regression models, and auto-regressive models (Moayedi & Mosavi, 2021). Researchers have used common wavelet transform fractal method (WTFM) for establishing correlation between H and PI of environmental factors.…”
Section: Short Reviewmentioning
confidence: 99%
“…Mirjalili et al ( 2014 ) proposed the metaheuristic algorithm grey wolf optimization (GWO) in 2014, a variant of the PSO with a metaphor, as proven in the recent works (Villalón et al, 2020 ). Similar to other metaheuristic approaches (Ala et al, 2020 ; Seifi et al, 2020 ; Moayedi and Mosavi, 2021a , b ), the algorithm is inspired by the social hierarchy and hunting strategies of gray wildlife wolves and it has been applied to various problems due to its simple idea (Heidari and Pahlavani, 2017 ; Aljarah et al, 2019 ; Heidari et al, 2019 ; Tang et al, 2020 ). Regardless of its defect, we still can see some performance features in this method (Niu et al, 2019 ; Hu et al, 2021 ).…”
Section: Enhanced Comprehensive Learning Particle Swarm Optimizermentioning
confidence: 99%